THE MODERN MANAGEMENT THEORY OF BUSINESS SUSTAINABILITY - S. Y. Kuznetsov (Стратегические решения и риск-менеджмент)
Business sustainability is a concept of resource-based theory of the firm. This theory explores the structure of its assets, its key capabilities, sustainable competitive advantage, differentiation and profitability. Due to differentiation there exists value-based management as an integrated accrued consumer solution, as an effective proposition of post-industrial value by a sustainable firm. The new pull-economy of a sustainable business gradually supplements and displaces push- microeconomy. Consumer is in the center of sustainable business organization, and customer relationship management is an important part of effective anti-crisis business strategy.